Bleeding Risk Profile in Patients on Oral Anticoagulation Undergoing Percutaneous Coronary Interventions: A Prospective 24 Months Cohort Study - Schukraft, Sara; Huwyler, Tibor; Ottiger-Mankaka, Cindy; Lehmann, Sonja; Cook, Ezia; Doomun, Daphné; Doomun, Ianis; Goy, Jean-Jacques; Stauffer, Jean-Christophe; Togni, Mario; Arroyo, Diego; Puricel, Serban; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background. The Academic Research Consortium have identified a set of major and minor risk factors in order to standardise the definition of a High Bleeding Risk (ACR-HBR). Oral anticoagulation is a major criterion frequently observed. Aims. The objective of this study is to quantify the risk of bleeding in patients on oral anticoagulation with at least one additional major ACR-HBR criteria in the Cardio-Fribourg Registry. Methods. Between 2015 and 2017, consecutive patients undergoing percutaneous coronary intervention were prospectively included in the Cardio-Fribourg registry. The study population included patients with ongoing long-term oral anticoagulation (OAC) and planned to receive triple antithrombotic therapy. Patients were divided in 2 groups: patients on OAC with at least one additional major ACR-HBR criteria vs. patients on OAC without additional major ACR-HBR criteria. The primary endpoint was any bleeding during the 24-month follow-up. Secondary bleeding endpoint was defined as Bleeding Academic Research Classification (BARC)≥ 3. Results. Follow-up was complete in 142 patients at high bleeding risk on OAC of which 33 (23%) had at least one additional major ACR-HBR criteria. The rate of the primary endpoint was 55% in patients on OCA with at least one additional ACR-HBR criteria compared with 14% in patients on OAC without additional ACR-HBR criteria (hazard ratio, 3.88; 95%CI 1.85-8.14; p<0.01). Patients with additional major ACR-HBR criteria also experienced significantly higher rates of BARC≥ 3 bleedings (39% at 24 months). Conclusion. The presence of at least one additional ACR-HBR criterion identifies patients on OAC who are at very high risk of bleeding after percutaneous coronary intervention.